Distribution of Galactomannan antigen in BAL and serum samples among Aspergillus isolates and its correlation with culture among Immunocompetent and Immunocomporomised patients in Aligarh region, a north India town - Roohani, Asma Husein; Fatima, Nazish; Shamim, Mohammad; Khan, Haris Manzoor; Akhtar, Anees (Annals of Pathology and Laboratory Medicine, 2019)
Background: Aspergillosis is one of the most common fungal infection among both general patients and immunocompromised individuals. Methods: The study was carried out on 2 groups of patients: immunocompetent and immunocompromised comprising of a total of 90 patients. Microscopy, culture, identification of isolates was done and some specialised tests on serum and BAL for antigen detection were performed. Result: Most of the patients i.e., 47 (31.3%) were between 31-40 years with a mean age of 32.5 years. The male to female ratio was 1.8:1. Galactomannan antigen was positive in 13 (28.9%) BAL samples and in 15 (33.3%) serum samples wherein the 45 BAL samples represented immunocompetent cases and 45 serum samples represented immunocompromised cases. Sensitivity and specificity of GM assay in BAL samples were found to be 100% and 97% respectively. On the other hand, sensitivity and specificity in serum samples were found to be 94.1% and 100% respectively. All patients were categorized into 4 categories as proven IPA, probable IPA, possible IPA and non-IPA. 22 (24.4%) patients were of proven invasive pulmonary aspergillosis (IPA), 7 (7.8%) of probable IPA, 2 (2.2%) belonged to possible IPA while 59 (65.5%) were of non IPA. All of the cases of proven IPA were positive on culture. Conclusion: GM assay in BAL is a very sensitive and specific marker for Aspergillosis while in case of serum samples it is somewhat lesser sensitive.